2015
DOI: 10.1037/a0038379
|View full text |Cite|
|
Sign up to set email alerts
|

Toward a meaningful metric of implicit prejudice.

Abstract: [Correction Notice: An Erratum for this article was reported in Vol 100(5) of Journal of Applied Psychology (see record 2015-40760-001). there are errors in some of the values listed in Table 6 that do not alter any of the conclusions or substantive statements in the original article. The corrected portion of Table 6 is in the correction. The positive intercepts in this table represent the estimated IAT score when the criterion has a value of zero (suggesting attitudinal neutrality), except in the equation exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 48 publications
1
54
1
Order By: Relevance
“…Blanton et al . () found that participants with neutral (non‐discriminatory) scores actually had positive (biased) IAT‐scores and concluded that the IAT must be right‐biased (e.g., showing too much bias) since it is not properly aligned with the discrimination outcome. They regard these discrimination outcomes as the gold standard to compare the IAT against (although they do admit that they have imperfections).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blanton et al . () found that participants with neutral (non‐discriminatory) scores actually had positive (biased) IAT‐scores and concluded that the IAT must be right‐biased (e.g., showing too much bias) since it is not properly aligned with the discrimination outcome. They regard these discrimination outcomes as the gold standard to compare the IAT against (although they do admit that they have imperfections).…”
Section: Discussionmentioning
confidence: 99%
“…The discussion has so far almost exclusively focused on either the conceptual link (e.g., does implicit bias predict discrimination) or on methodological issues with the IAT (e.g., if the zero point is meaningful; Blanton et al ., ). In the present research, we will switch the focus to the discrimination outcomes themselves.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Relying on zero-order correlations between the IAT and all criteria in general is too crude and begs the fundamental question of the behavioral implications of different IAT scores (Blanton, Jaccard, & Burrows, 2015;Blanton, Jaccard, Strauts, Mitchell, & Tetlock, 2015). Greenwald et al (2015) offer two examples that they contend illustrate how the average effect size estimates for race IATcriterion correlations might have real-world consequences.…”
Section: The Importance Of Effect Size Heterogeneitymentioning
confidence: 97%
“…Blanton et al (2006) found evidence against the assumption of equal b 2 and b 4 weights for the IAT and, indeed, Greenwald, Nosek, and Banaji (2003) offered a scoring algorithm, in part, as an explicit acknowledgment of the problem. Unfortunately, the new scoring algorithm adjusts for GPS in ways that introduce a host of new problems (see Blanton, Jaccard, Strauts, Mitchell, & Tetlock, 2015).…”
Section: Downloaded By [University Of Lethbridge] At 13:46 03 Octobermentioning
confidence: 99%